Ensayo sobre argumentación jurídica, derechos fundamentales y personas jurídicas -Análisis doctrinario, jurisprudencial y normativo- - Castilla Colquehuanca, Jhoni Shang (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2023)
This work, which can very well be considered as a manual (as it deals with issues related to the understanding or introduction to the study of legal argumentation and fundamental rights today), starting from the premise that the Legal argumentation is very important in the different legal fields or contexts in which it occurs, and, precisely, reviewing the doctrinal, jurisprudential and normative argumentation, it addresses the problem of ownership of fundamental rights by legal persons.